Spongiaires d'Afrique du Sud. (1) Poecilosclérides - Lévi, C. (Transactions of the Royal Society of South Africa, 1963)
Little is known of South African sponges. Large collections with notes on habitatll have recently been made by the University of Cape Town Ecological Survey under the direction of Professor J. H. Day. This paper, which is the first of a series, deals with 75 species of Demospongia Poecilosclerida of which 38 are new. The description of other groups will be followed by a general discussion of the distribution of these sessile animals.